2018
DOI: 10.3389/fpls.2018.01655
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Biostimulatory Action: Designing the Next Generation of Plant Biostimulants for Sustainable Agriculture

Abstract: Over the past 10 years, interest in plant biostimulants (PBs) has been on the rise compelled by the growing interest of scientists, extension specialists, private industry, and growers in integrating these products in the array of environmentally friendly tools that secure improved crop performance and yield stability. Based on the new EU regulation PBs are defined through claimed agronomic effects, such as improvement of nutrient use efficiency, tolerance to abiotic stressors and crop quality. This definition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
235
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 347 publications
(247 citation statements)
references
References 60 publications
(79 reference statements)
8
235
0
4
Order By: Relevance
“…The positive effects of the foliar application of LDPH, irrespective of the N fertilization treatments, were more pronounced in spinach than in lamb's lettuce, demonstrating a species-specific response [15,55], especially that the same commercial plant-based biostimulant was used. The different responses between the two leafy vegetables species could be attributed to the different leaf permeability and cuticle morphology as well as the stomatal aperture and thus the efficacy of the plant biostimulant [38]. Therefore, our results highlight, that further study is warranted to assess the physiological and molecular mechanisms behind the biostimulant action and to investigate the specificity of species dependent responses in impacting leaf characteristics and consequently interacting with the different bioactive compounds of plant biostimulants.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The positive effects of the foliar application of LDPH, irrespective of the N fertilization treatments, were more pronounced in spinach than in lamb's lettuce, demonstrating a species-specific response [15,55], especially that the same commercial plant-based biostimulant was used. The different responses between the two leafy vegetables species could be attributed to the different leaf permeability and cuticle morphology as well as the stomatal aperture and thus the efficacy of the plant biostimulant [38]. Therefore, our results highlight, that further study is warranted to assess the physiological and molecular mechanisms behind the biostimulant action and to investigate the specificity of species dependent responses in impacting leaf characteristics and consequently interacting with the different bioactive compounds of plant biostimulants.…”
Section: Discussionmentioning
confidence: 84%
“…Several researches have highlighted that plant-based biostimulants have a triggering effect on growth and yield, but they are also capable of improving the NUE in consideration of both economic and environmental motives [38,51]. The plant-based biostimulant used in this test was Trainer ® , a legume-derived protein hydrolysate (containing free amino acids and signaling molecules such as small soluble peptides), for which previous researches have already demonstrated its ability to boost crops' resources use efficiency (RUE) [15,52]-especially N uptake and assimilation [39]-as well as productivity [6,32] and quality [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Plant biostimulants are defined as products obtained from different organic or inorganic substances and/or microorganisms, that are able to improve plant growth, productivity and alleviate the negative effects of abiotic stresses [56,57]. Mineral elements, vitamins, amino acids, and polyand oligosaccharides, trace of natural plant hormones are the most known components.…”
Section: Biostimulantsmentioning
confidence: 99%
“…Humic substances (HSs): they include humic acids, fulvic acids and humins. HSs are natural constituents of soil organic matter, resulting from the decomposition processes of plants, animals, and microbial residues, but also from the metabolic activity of soil microbes [57]. It has been observed that treatments with humic substances stimulate plants root growth and development [64,65].…”
Section: Classification Of Biostimulants In Categoriesmentioning
confidence: 99%
“…A recent systematic approach highlights the contribution of investigation and understanding of biostimulant 2 of 19 mechanisms and their mode of action [10]. This work includes comprehensive reviews on economic and environmental benefits of biostimulant use, obtainment of higher yields of cultivated plants with improved quality, decreasing of nitrate level according to EU regulation, reducing energy consumption and utilizing resources more efficiently [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%